Outdoor thermal perception in different climatic regions. Initial results from Taichung (Taiwan) and Lisbon (Portugal) - Lin, Tzu-Ping; Andrade, Henrique; Oliveira, Sandra; Hwang, Ruey-Lung; Matzarakis, Andreas (Finisterra, 2014)
People living in different climatic regions have adapted to specific weatherconditions and their tolerance to high temperatures and wind speeds is diverse. This studyanalyses the effect of thermal adaptations on the thermal perception of users of outdoorspaces in two different regions: Taichung (Taiwan) and Lisbon (Portugal), by means of fieldsurveys and measurements of weather parameters. The thermal acceptable range, representingthe satisfaction of people with thermal conditions, was calculated based on the PhysiologicalEquivalent Temperature (PET) and the results obtained for each region were compared.People in Lisbon are less satisfied with higher values of PET than in Taiwan, due tothe adaptation of local people to higher values of air temperature and relative humidity inTaiwan. On the contrary, people in Lisbon showed a higher tolerance to strong wind, as aresult of their exposure to higher average wind speeds than those in Taiwan. The resultsdemonstrated that people’s thermal perceptions vary with different climatic and culturalbackground. The influence of thermal adaptations in the use of outdoor spaces can contributeto improve the quality of these spaces, adapting them to the preferences of local users.